Pengelolaan Wilayah Pesisir Indonesia dalam Rangka Pembangunan Berbasis Pelestarian Lingkungan - Tommy Cahya Trinanda (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
Indonesia is a country with the second longest shoreline in the world after Canada. Regardless, the management of coastal areas with the said length havn’t optimized yet and evenly that only 55 percent of potential available sources was used. Development on all sectors in coastal areas has marginalized the local society that on average work as traditional fishermen and has ruled out the preservation of enviromental ecosystem and natural habitat. The purpose of this study was to find out the ideal formulation of coastal management based on conservation. The research method used is normative juridical analysis method. The research aim tho show that the management coastal areas between sectors is still not well integrated. Therefore, it needs a policy that regulate various aspects on coastal areas management for the welfare of the people in the coastal area and archipelago.